Evaluation of the Finnish nuclear waste management programme : report of the WATRP review team - Kauppa- ja teollisuusministeriö. Energiaosasto; International Atomic Energy Agency (Kauppa- ja teollisuusministeriö, ISSN 0788-8546, 1994)
Abstract (s. 5-6, kuvailulehti).
Keywords: ydinjätteet : jätehuolto